Gaya Kepemimpinan Ustadz di Pondok Pesantren Al-Mubarok Sumur Pecung Kecamatan Serang Kota Serang - Setiawan, Adam; Hanafi, Syadeli; Fauzi, Ahmad (EDU SOCIATA ( JURNAL PENDIDIKAN SOSIOLOGI ), 2025)
Leadership in Islam is an interesting topic for discussion and a skill that every leader must possess in order to lead a group, whether it be an organization or not. This study aims to examine the leadership style of the ustadz at the Al-Mubarok Islamic boarding school in Sumur Pecung, Serang District, Serang City. The research method used is a descriptive qualitative approach through field observations, interviews with leaders and students, and documentation. The results of this study indicate that the leadership style of ustadz suggests that an ideal leader should possess the ability to provide guidance, direct, motivate, and inspire their subordinates to achieve the desired goals. However, there are several challenges, such as the lack of understanding among students regarding the implementation of the ustadz's leadership style. Recommendations are provided to strengthen the understanding of the ustadz's leadership style at the Al-Mubarok Islamic Boarding School.